2021
DOI: 10.1007/s00428-021-03244-w
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for diagnosing STIC: a systematic review and meta-analysis

Abstract: Our understanding of the oncogenesis of high-grade serous cancer of the ovary and its precursor lesions, such as serous tubal intraepithelial carcinoma (STIC), has significantly increased over the last decades. Adequate and reproducible diagnosis of these precursor lesions is important. Diagnosing STIC can have prognostic consequences and is an absolute requirement for safely offering alternative risk reducing strategies, such as risk reducing salpingectomy with delayed oophorectomy. However, diagnosing STIC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…In general, diagnosing STIC is challenging with only moderate reproducibility. A recently published systematic review suggests not only the use of the SEE-FIM protocol, but also evaluation by a subspecialized pathologist, rational use of immunohistochemical staining, and obtaining a second opinion from a colleague to secure the diagnosis ( 41 ). Furthermore, there can also be a HGSC unrelated to a STIC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In general, diagnosing STIC is challenging with only moderate reproducibility. A recently published systematic review suggests not only the use of the SEE-FIM protocol, but also evaluation by a subspecialized pathologist, rational use of immunohistochemical staining, and obtaining a second opinion from a colleague to secure the diagnosis ( 41 ). Furthermore, there can also be a HGSC unrelated to a STIC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, precursor lesions in fallopian tubes removed from women with a genetic predisposition to ovarian cancer are identified by trained pathologists. Since visual morphologic changes in precursor lesions are subtle, interpretations by pathologists are unavoidably subjective ( 9 , 40 ). Yet, it is important to establish the correct diagnosis because women with isolated premalignant lesions in the fallopian tube are at increased risk of developing carcinomatosis, presumably because cancer cells have spread from the precursor lesion to other organs in the peritoneal cavity prior to preventive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological features for diagnosing STIC have been variably applied by pathologists, 6 and studies have shown that establishing a diagnosis using only morphology does not have high interobserver reproducibity. [17][18][19][20] Thus, a diagnostic algorithm that incorporates histological features coupled with immunohistochemical results for p53 and Ki-67 (Figure 3) was previously developed to aid the classification of epithelial atypias of the fallopian tube, which improves the reproducibility of diagnosing STIC 18,19,21 and allows lesions to be categorised as STIC, atypical lesions intermediate between STIC and p53 signature (serous tubal intra-epithelial lesion [STIL]; lesions analogous to STIL have been described by various terms in other publications, such as dysplasia, tubal intra-epithelial lesion in transition and dormant STIC [the designation dormant STIC has been used in other studies to designate lesions with significant atypia and aberrant p53 expression but without a high Ki-67 proliferation index (see below for thresholds separating low from high indices)] and p53 signature (see Pathogenesis section below).…”
Section: Combined Use Of Histological and Immunohistochemical Feature...mentioning
confidence: 99%
“…During the last 20 years an accumulation of voluminous data from multiple clinicopathological, immunohistochemical and molecular studies has shed light on this topic, and elucidated serous tubal intraepithelial carcinoma (STIC) of the fallopian tube as being a precursor for the vast majority of high-grade serous carcinomas of the ovary, fallopian tube and peritoneum. [1][2][3][4][5] However, criteria for diagnosing STIC have varied among multiple investigational studies; 6 thus, the uniform use of criteria is needed to facilitate communication among pathologists. This will be necessary in order to more reproducibly diagnose STIC for reporting purposes, as well as to improve accuracy for classification in research studies and determine the natural history of this lesion.…”
Section: Introductionmentioning
confidence: 99%